Metodología del proyecto comunicando-ando. - Aucatoma Arias, Richard Wladimir (2016)
The creation of Communication Projects created by students of Universidad Politécnica Salesiana has allowed strengthening and putting at the service of community the acquired knowledge in the institution, performing projects of medium and big scale in favor of human development. So, it is necessary the planning which uses as a manner, a methodology or phases to follow, thus achieving intervene effectively to act on a reality with a charitable purpose. The audiovisual project lists: interviews with direct beneficiaries, performers, teachers, and didactically, the methodology used in the "Comunicando-Ando" Project performed by students of Social Communication major with emphasis to the result gotten from entrepreneurship by beneficiary teenagers. The "Como un juego de Dados" Product will be a resource of didactic support for teachers and students.